2019
DOI: 10.1002/pds.4725
|View full text |Cite
|
Sign up to set email alerts
|

Rates of reported codeine‐related poisonings and codeine prescribing following new national guidance in Ireland

Abstract: Purpose The aims of this study were to examine a national database to assess codeine poisonings before and after the new guidance for pharmacists while also evaluating rates of codeine prescriptions following the introduction of restrictions on supply. Methods Anonymised enquiry data of reported poisoning cases were reviewed for a period from 2005 to 2016 inclusive. The rate of pharmacy claims for codeine containing products was also examined using the national pharmacy claims database. Segmented regression an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 23 publications
0
17
0
1
Order By: Relevance
“…Six studies used retrospective analysis of databases to report the misuse of 4 individual OTC medicines, including codeine, loperamide, dextromethorphan (DXM) and paracetamol. Two studies, one in Australia [ 27 ] and the other in Ireland [ 28 ] investigated the trend of codeine misuse and assessed the effect of restricting codeine supply on the misuse rate. In Australia, from 2004 to 2015, the average annual percentage change for codeine/paracetamol preparation misuse was 19.5% and for codeine/ibuprofen was 17.9% [ 27 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Six studies used retrospective analysis of databases to report the misuse of 4 individual OTC medicines, including codeine, loperamide, dextromethorphan (DXM) and paracetamol. Two studies, one in Australia [ 27 ] and the other in Ireland [ 28 ] investigated the trend of codeine misuse and assessed the effect of restricting codeine supply on the misuse rate. In Australia, from 2004 to 2015, the average annual percentage change for codeine/paracetamol preparation misuse was 19.5% and for codeine/ibuprofen was 17.9% [ 27 ].…”
Section: Resultsmentioning
confidence: 99%
“…In Australia, from 2004 to 2015, the average annual percentage change for codeine/paracetamol preparation misuse was 19.5% and for codeine/ibuprofen was 17.9% [ 27 ]. In Ireland, The National Poisons Information Centre (NPIC) received 1,851 codeine-containing product poisoning calls from 2005 to 2016, whilst the OTC codeine comprised 70% of these cases [ 28 ]. The rate of misuse of paracetamol combination products was found at 0.06% (per 1000,000 population per 10 years) through data reported to the American National Poison Data System (NPDS) from 2007 to 2016 [ 29 ].…”
Section: Resultsmentioning
confidence: 99%
“…Other pharmacists felt that rescheduling to Schedule 3 prompted them to upskill in the area of pain management [23]. Following the second up-scheduling to Schedule 4 for any product containing codeine, it was reported that the up-scheduling actually created an opportunity for patients to openly discuss their pain issues with the pharmacist and seek non-codeine strategies to manage their pain [23,24].…”
Section: Marketing and Advertisingmentioning
confidence: 99%
“…In addition, it was reported that when codeine was regulated to Schedule 3, some pharmacists were concerned about their clinical competence not being sufficient to help patients with pain management without the aid of over-the-counter CCPs [24]. It was consistent in most of the studies that the up-scheduling of codeine required additional educational training for pharmacists in the area of pain management, counseling skills, and the handling of drug misuse [13,23,24]. This could imply that, if a change in CMs scheduling were to eventuate, pharmacists, pharmacy assistants, and pharmacy technicians would need to undertake professional training in the area of CMs to build on their evidence-based CMs knowledge.…”
Section: Marketing and Advertisingmentioning
confidence: 99%
“…Com relação ao número de notificações segundo a raça dos adolescentes, observou-se um maior número de intoxicações em adolescentes da raça branca, com 79.409 (= 40,03%) casos notificados, seguida da raça parda, com 68.504 (= 34,53%) conforme mostra a Tabela 3. Research, Society and Development, v. 9, n. 10, e6349108914, 2020 (CC BY 4.0 (Kennedy, Duggan, Bennett, & Williams, 2019).…”
Section: Metodologiaunclassified